Lactide polymerisation by ring-expanded NHC complexes of zinc. (8th January 2016) - Collins, Lee R.; Moffat, Louise A.; Mahon, Mary F.; Jones, Matthew D.; Whittlesey, Michael K.
Graphical abstract: The activity of ring-expanded N-heterocyclic carbene complexes of zinc for the ring-opening polymerisation of rac -lactide has been probed alongside that of the free carbenes. Abstract: The reaction of the ring-expanded N-heterocyclic carbenes (RE-NHCs) with [ZnMe2 ] affords the structurally characterised complexes [(6-Mes)ZnMe2 ] (1 ) and [(7-Mes)ZnMe2 ] (2 ). The activity of the two complexes, along with that of the free carbenes, for the ring-opening polymerisation of rac -lactide has been probed. Even for such strongly σ-donating carbenes, dissociation from the metal centre cannot be ruled out.